2010
DOI: 10.4018/jhisi.2010040101
|View full text |Cite
|
Sign up to set email alerts
|

Random Forest Classifier Based ECG Arrhythmia Classification

Abstract: Heart Rate Variability (HRV) analysis is a non-invasive tool for assessing the autonomic nervous system and for arrhythmia detection and classification. This paper presents a Random Forest classifier based diagnostic system for detecting cardiac arrhythmias using ECG data. The authors use features extracted from ECG signals using HRV analysis and DWT for classification. The experimental results indicate that a prediction accuracy of more than 98% can be obtained using the proposed method. This system can be fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Some existing studies have demonstrated that random forest classification (RFC) can be well adopted for medical disease classification, habitat identification in ecological environments, and land cover classification based on multispectral images [23][24][25]. For the UAV multispectral images in this study, RFC was implemented to differentiate between vegetation and soil, and then created a vector including corn vegetation and soil.…”
Section: Image Processingmentioning
confidence: 99%
“…Some existing studies have demonstrated that random forest classification (RFC) can be well adopted for medical disease classification, habitat identification in ecological environments, and land cover classification based on multispectral images [23][24][25]. For the UAV multispectral images in this study, RFC was implemented to differentiate between vegetation and soil, and then created a vector including corn vegetation and soil.…”
Section: Image Processingmentioning
confidence: 99%
“…The abstract and artificial features constituted a feature vector for yielding the fused feature matrix. Finally, a random forest [ 24 ] containing 300 decision trees was employed to classify the AF segments. Figure 2 shows the flowchart of the proposed method.…”
Section: Methodsmentioning
confidence: 99%
“…They reached an accuracy of 89% validated with fivefold cross validation. Similar random forest classifiers for ECG classification were developed by Sathish & Vimal [64], or Emanet [65].…”
Section: Random Forestsmentioning
confidence: 99%